2022
DOI: 10.1371/journal.pone.0264062
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis vaccination adherence and completion rates and factors associated with low compliance: A claims-based analysis of U.S. adults

Abstract: Poor compliance with multi-dose vaccine schedules by adults for whom hepatitis (Hep) A and B vaccines are recommended contributes to major Hep A and B disease burdens among high-risk U.S. adults. Evidence on hepatitis vaccine series adherence, completion, timeliness of completion, and factors associated with these outcomes, is limited and not readily generalizable for U.S. adults. This retrospective, observational study examined adherence, completion, its timeliness, and the impact of sociodemographic and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…These findings support a recent study that found lower rates of HBV vaccination adherence to be associated with lower educational attainment ( LaMori et al, 2022 ). Our results also support previous research conducted in different locations and with different populations that highlights the lower HBV vaccination coverage among Hispanics and African Americans when compared to whites ( Bhuiyan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…These findings support a recent study that found lower rates of HBV vaccination adherence to be associated with lower educational attainment ( LaMori et al, 2022 ). Our results also support previous research conducted in different locations and with different populations that highlights the lower HBV vaccination coverage among Hispanics and African Americans when compared to whites ( Bhuiyan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Among individuals who received the 2-dose vaccine series, Heplisav-B, adherence rates were more than 2-fold higher (32.2%) than in individuals who received traditional 3-dose (Engerix-B and Recombivax-HB) HBV vaccines (14.3%). This difference in adherence rates was consistent across all age groups 27. Supplemental data further highlighted vaccination adherence and completion (24 months) rates for hepatitis A, hepatitis B (3-dose series), and combination hepatitis A and B vaccines (3-dose series) among special at-risk or high-risk populations with chronic comorbidities (diabetes with and without chronic complications, mild to severe liver disease, and renal disease).…”
supporting
confidence: 54%
“…While protein subunit vaccines have been successfully applied against a limited number of pathogens, logistical challenges, including high production costs and the need for three or more immunizations, have hindered their broader application. [45][46][47] The advent of mRNA LNP vaccines, exemplified by the rapid development and distribution to combat the COVID-19 pandemic, offers a promising solution to address these challenges. 36,37 mRNA-1273 and BNT162b2, developed under "Project Lightspeed," were swiftly distributed, significantly reducing hospitalizations and fatalities caused by SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%